ABDOMINAL BLUNT INJURY AMONG PREGNANCY - I Gede Egy Saputra Jaya; Ketut Putera Kemara; I Wayan Megadhana (E-Jurnal Medika Udayana, 2013)
Pregnancy is an important event that blissful for pregnant women, but it can be changed when bad things happen on the pregnancy. Trauma to the pregnant women is one of the most cause of the non-obstetic tresulting in morbidity and mortality in pregnancy by 6-7% on the whole pregnancy. The death of the fetus even more happened many compared with mortality pregnant at gets reinjured because trauma, which reached 65 %. Unique changes in anatomy and Physiology during pregnancy change the pathophysiology and the location of trauma to pregnant women. For doctors, this poses challenges because care must be devoted to two patients, the mother and fetus that it contains. This can be resolved more easily if the doctors understand the changes in anatomy, Physiology, mechanisms of injury and trauma assessment in pregnant women.